THE ROLE OF CERTIFICATES AS EVIDENCE OF LAND RIGHTS TOWARDS THE ERA OF REVOLUTION 4.0 - Maiyestati Maiyestati (Universitas Slamet Riyadi, 2021)
Considering the very importance of the use of land for people or business entities that demand legal certainty over the land, the formulation of the problem in this study is stated: how is the role of certificates as evidence of land rights in the era of revolution 4.0?. The type of research used to solve the problem in this study was juridical-normative, with qualitative analysis. The role of certificates as an evidence of land rights in the 4.0 revolution era in Indonesia is only a strong sign and is not an absolute evidence, with a negative system that contains positive elements. A certificate that has been legally issued in the name of a person or legal entity of another party who admit for the right may file a written objection to the certificate holder and to the Land Office.